ANALISIS YURIDIS PERBANDINGAN HUKUM TENTANG ROKOK ELEKTRIK DI INDONESIA DAN SINGAPURA - Richard Stevanus Sitio (JISOS: JURNAL ILMU SOSIAL, 2023)
E-cigarettes are one type of cigarette that is more modern and widely used today. The widespread use of e-cigarettes certainly encourages many parties to ask about the rules governing these e-cigarettes. The research is a study conducted to find out the comparison of laws governing the use of e-cigarettes in Indonesia and Singapore. The method used is the juridical analysis method, which means analyzing the rules that apply regarding e-cigarettes in Indonesia and Singapore. The results found that e-cigarettes in Singapore have very strict regulations, even the activity of importing e-cigarettes is illegal. While Indonesia has slightly loose regulations regarding e-cigarettes